2017
DOI: 10.1111/jcpe.12816
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of peri‐implantitis: Prognostic indicators of short‐term results

Abstract: Aim: To evaluate the clinical and radiographic short-term (6 months) effect of surgical treatment of peri-implantitis, and to identify prognostic indicators affecting the outcome using a multilevel statistical model. Materials & Methods:A total of 143 implants (45 patients) with a diagnosis of progressive peri-implantitis (progressive bone loss (PBL) ≥2.0 mm and bleeding on probing (BoP)/suppuration) received surgical treatment. Clinical and radiographic parameters were assessed 6 months postoperatively. Poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 30 publications
5
48
0
1
Order By: Relevance
“…Following treatment, BOP was yet measured at 90% of sites in both groups after either therapies. Noticeable variations between the incidence of BOP and clinically manifested peri-implantitis was previously reported (Mombelli, Muller, & Cionca, 2012 (Koldsland, Wohlfahrt, & Aass, 2018). Both findings in addition to the results of the current study agree with the conclusions of a recent systematic review; that the extent to which BOP can identify peri-implantitis seems to be limited (Hashim, Cionca, Combescure, & Mombelli, 2018).…”
Section: Principal Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Following treatment, BOP was yet measured at 90% of sites in both groups after either therapies. Noticeable variations between the incidence of BOP and clinically manifested peri-implantitis was previously reported (Mombelli, Muller, & Cionca, 2012 (Koldsland, Wohlfahrt, & Aass, 2018). Both findings in addition to the results of the current study agree with the conclusions of a recent systematic review; that the extent to which BOP can identify peri-implantitis seems to be limited (Hashim, Cionca, Combescure, & Mombelli, 2018).…”
Section: Principal Findingssupporting
confidence: 92%
“…Noticeable variations between the incidence of BOP and clinically manifested peri‐implantitis was previously reported (Mombelli, Muller, & Cionca, ). More recently, another group reported that following surgical peri‐implantitis therapy, no BOP was demonstrated in only 14% of implants treated, and almost only 2% at patient level (Koldsland, Wohlfahrt, & Aass, ). Both findings in addition to the results of the current study agree with the conclusions of a recent systematic review; that the extent to which BOP can identify peri‐implantitis seems to be limited (Hashim, Cionca, Combescure, & Mombelli, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 10 articles were included in this review. Six prospective randomized controlled trials, 9,10,16-18, 22 1 prospective cohort study, 8 2 retrospective controlled studies, 15,23 and 1 case series 24 were designed with follow-up periods of 6 months, 9,24 1 year, 8,10,15,22,23 and 3 years. [16][17][18] The risk of bias across studies was classified as unclear risk in 5 cases (1 or more criteria missing), 8,9,17,18,22 as moderate risk in 1 case, 10 and as high risk in 4 studies (2 or more criteria missing).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical scaling with periodontal hand scalers and ultrasonic tips is the most common treatment of periodontal and peri-implant tissue infections. [ 7 9 10 ] Periodic scaling and cleaning of biofilm accumulation niches are a noninvasive option, acting in prevention and production of excellent clinical results. [ 7 11 12 13 ] In general, the combination of this control therapy associated with instruction and patient hygiene motivation culminates in preventing the disease progression.…”
Section: Introductionmentioning
confidence: 99%